2010
DOI: 10.1007/s11111-010-0122-0
|View full text |Cite
|
Sign up to set email alerts
|

If you build it, will they come? Biofuel plants and demographic trends in the Midwest

Abstract: The rural United States has suffered long-term population decline over the past several decades, especially in farming communities. In recent years, biofuel production has been argued to hold potential for the revitalization of rural America and in response, many rural communities have eagerly attempted to attract ethanol plants as a local development effort. This study conceptualizes economic revitalization in terms of population dynamics and investigates whether the establishment of a biofuel plant has been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Także tworzenie miejsc pracy było postrzegane jako kluczowe, stąd w niektórych pracach w zasadzie stawiano znak równości między odnową a nowymi miejscami pracy (zob. Keane, Garvey 2005;Lehrer 2010;Gkartzios, Norris 2011;Kulscar, Bolender 2011). Wreszcie ważną rolę przypisywano turystyce na obszarach wiejskich jako formie gospodarki zorientowanej na konsumpcję (Rofe 2012).…”
Section: Perspektywa Anglosaska -Rozwój Społeczności Kluczem Do Ekonomicznej Regeneracji Obszarów Wiejskichunclassified
“…Także tworzenie miejsc pracy było postrzegane jako kluczowe, stąd w niektórych pracach w zasadzie stawiano znak równości między odnową a nowymi miejscami pracy (zob. Keane, Garvey 2005;Lehrer 2010;Gkartzios, Norris 2011;Kulscar, Bolender 2011). Wreszcie ważną rolę przypisywano turystyce na obszarach wiejskich jako formie gospodarki zorientowanej na konsumpcję (Rofe 2012).…”
Section: Perspektywa Anglosaska -Rozwój Społeczności Kluczem Do Ekonomicznej Regeneracji Obszarów Wiejskichunclassified
“…Gains in efficiency also are seen through farm consolidation. While consolidation typically increases production volumes, it concurrently displaces farm populations (Kulcsár and Bolender, 2011). When there is a relative lack of alternative employment opportunities, as is commonly the case in farm-dependent counties, outmigration typically occurs (Johnson and Rathge, 2006).…”
Section: Population and Migration Patterns In The Prairie Pothole Regmentioning
confidence: 99%
“…Farm consolidation in stride with technological advances has increased production volumes while reducing demand for hired farm labor and displacing farmers and their families. A weak off-farm economy in an area experiencing farm consolidation is likely to fall into continuous outmigration and negatively impact local employment opportunities (Kulcsár and Bolender, 2011). Literature findings suggest the decline in farm employment largely is a result of changes in farming itself; not necessarily a result of outside stressors.…”
mentioning
confidence: 99%
“…Demographic research has also indicated that the presence of a biofuels plant shows little association with population growth. Instead, such developments typically occur in places with already existing capacity, and hence perpetuate spatial inequalities rather than reversing depopulation (Kulcsar and Bolender, 2011).…”
Section: Introductionmentioning
confidence: 99%